A jurisprudential and legal research into the oath of knowledge denial - Ã™Â…Ã˜Â§Ã™ÂÃ›ÂŒ, Ã˜Â¯ÃšÂ©Ã˜ÂªÃ˜Â± Ã™Â‡Ã™Â…Ã˜Â§Ã›ÂŒÃ™ÂˆÃ™Â†; Ã˜Â±Ã˜Â¶Ã˜Â§Ã›ÂŒÃ›ÂŒ Ã™Â…Ã™Â‚Ã˜Â¯Ã™Â…, Ã˜Â±Ã˜Â¶Ã˜Â§ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Among the topics discussed in books of jurisprudence is denial of knowledge, which is considered as a subdivision of taking oath based on issue. Regardless of the originality of oath on denying knowledge, substantial disagreement is discernible in jurisprudence as regards the establishment of legal provisions on this type oath-taking, very few of which opinions have influenced jurists in this field. In cases where the subject of dispute is an issue attributed to others or includes external features - knowledge of which is difficult for ordinary people - and in the inaccessibility to reasons, the claimant can only take the defendant under oath when he has claimed knowledge in that relation. By taking the oath of knowledge denial, the defendant will also be exempted from taking a strong (batti) oath on denying the right of the claimant; therefore, it can be said that a knowledge denial oath is essentially responsive by nature and uttered by the defendant in response to claims of knowledge.